English Learning Based on Open Space for Communities in Tana Toraja District - Nehru Pasoloran Pongsapan (Publikasi dan UKI Press UKI Toraja., 2019)
The objective of this research is to find out the problem faced by the fourth semester Educators at the university, high school and academy levels have the obligation to carry out the tri-services of tertiary institutions, namely (1) education and teaching, (2) research in the context of developing science and (3) carrying out community service based on the field of science and technology in accordance his/her discipline. Likewise, lecturers in the English Language Study Program, have the competence to carry out